Comparative pharmacoeconomic analysis of Paclical® and Taxol® in Russian Federation - A. E. Cheberda; D. Yu. Belousov (Качественная клиническая практика, 2018)
Ovarian cancer is a severe oncological disease, characterized by relatively late detection and unfavorable course leading to significant mortality among affected patients. One of the most well-proven treatment strategies is combination of taxanes such as Paclitaxel with platinum compounds. Unfortunately physicochemical properties of Paclitaxel (Taxol®) necessitate using it with an expensive, highly allergenic and hard to manage emulsifier that requires an extensive premedication regime before administration. A recently developed technology for micronizing Paclitaxel has allowed to create a new drug form, Paclical®, which allows to carry out chemotherapy without a need for complex premedication and specialized infusion systems. Available randomized clinical trial data indicates that Paclical® is not inferior to Taxol® in terms of safety and efficacy. Since taxanes are in high demand in oncology, it appears worthwhile to carry out a pharmacoeconomic comparison of Paclical® and Taxol®, which is the subject of current research effort. Aim. To perform the pharmacoeconomic analysis of Paclical® and Taxol® as adjuvants for Carboplatine for patients with recurrent epithelial ovarian cancer within context of Russian Healthcare. Methodology. This PHe is conducted perspective of public health organizations of the RF at federal and national levels, as well as from general social interest perspective. A complex PHe model consisting of a “decision tree” (to model treatment proper) and a Markov model (to model survival without progression over timespan of 12 months) was constructed. Cycle length for the Markov component of the model was set at 1 month. Two groups composed of 1000 patients each was simulated, each receiving one of the investigated drugs in combination with carboplatine, as well as full set of diagnostic and therapeutic interventions as outlined in relevant Russian standards. Randomized clinical trial dedicated to safety, tolerability and efficacy of the investigated compounds was used as data source. Direct medical costs in each simulated group were estimated using existing standards. Indirect costs including GDP loss and disability payments were also accounted for. Cost-effectiveness analysis, Cost-minimization analysis, Budget impact analysis, pharmacoeconomic expediency assessment and sensitivity analysis were performed. Result. Cost-minimization indicator for Paclical® was determined to be -3 544 819 rub., indicating reduction of direct costs when using this drug. Paclical® also dominated in terms of CER (259 703,5 rub. for Paclical® and 306 852,6 rub. for Taxol®), and since use of Paclical® was associated with both increased effectiveness and cost reduction, ICER calculation was not necessary. Overall number of patients surviving without progression at 12-month mark was used as efficacy criterion. Budget impact analysis has found that Paclical® is associated with reduction of budgetary burden, specifically a 3,6% saving that corresponds to 130 919 rub. per 100 000 of population (adjusted for ovarian cancer incidence). Pharmacoeconomic expediency assessment indicated that both drugs are acceptable for purposes of drug reimbursement system but Paclical® is somewhat more appealing due to wTP/CER indicator of 5,7 (with Taxol® having 4,8). Sensitivity analysis has confirmed the robustness of these findings Conclusion. Use of Paclical® is associated with higher healthcare resources utilization efficiency due to Paclical®’s domination in terms of CER indicator, as well as direct cost reduction of 3 544 819 rub., better absolute progression-free survival at 12-month mark, and reduction of budgetary burden by 3,6% per 100 000 of population. Both drugs being investigated are acceptable as part of drug reimbursement system but Paclical® is slightly more attractive. Thus, use of Paclical® in Russian oncological patients with ovarian cancer appears highly expedient.